Ontologies and the Semantic Web - Horrocks, I (2008)
Semantic web research aims to help web-accessible information and services be more effectively used, particularly by software agents and applications. The World Wide Web Consortium (W3C) has developed new languages, including RDF and OWL, that allow for the description of web resources and the representation of knowledge to enable applications to use resources more intelligently. RDF is a language that provides a flexible mechanism for describing web resources and the relationships among them. The RDF specification extends the capabilities of the language by giving additional meaning to certain resources. OWL is another language, which has its basis in Description Logics, a family of logic-based knowledge-representation formalisms that are descendants of semantic networks. Semantic web research has a major influence on the development and deployment of ontology languages and tools. It plays an important role where the information has a high value and where information is incomplete.